PsycEXTRA Dataset 2011
DOI: 10.1037/e529622011-001
|View full text |Cite
|
Sign up to set email alerts
|

One Year Longitudinal Study of the Psychological Effects of Administrative Segregation

Abstract: The researchers would also like to acknowledge the support of Mr. Aristedes Zavaras and the staff at the Department of Corrections. This project would never have been possible without the commitment and contributions of management, mental health, case management, offender services, and security staff.This document is a research report submitted to the U.S. Department of Justice. This report has not been published by the Department. Opinions or points of view expressed are those of the author(s) and do not nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 83 publications
5
105
1
Order By: Relevance
“…Based on the results of the current study, it is speculated that the ensnarement hypothesis provides a superior explanation of the association between within‐prison sanctioning and recidivism relative to the deprivation hypothesis (Tannenbaum, ). Given the evidence suggesting that disciplinary segregation has limited effects on the psychological status of inmates, which is a fundamental component of deprivation theory, one could argue that alternative mechanisms (e.g., ensnarement) mediate the association between within‐prison sanctioning and recidivism (O'Keefe et al., , O'Keefe et al., ). In comparison to deprivation theory, the ensnarement hypothesis does not rely upon the manifestation of psychological harms but rather argues that within‐prison sanctions generally limit the prosocial opportunities of inmates (Moffitt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the current study, it is speculated that the ensnarement hypothesis provides a superior explanation of the association between within‐prison sanctioning and recidivism relative to the deprivation hypothesis (Tannenbaum, ). Given the evidence suggesting that disciplinary segregation has limited effects on the psychological status of inmates, which is a fundamental component of deprivation theory, one could argue that alternative mechanisms (e.g., ensnarement) mediate the association between within‐prison sanctioning and recidivism (O'Keefe et al., , O'Keefe et al., ). In comparison to deprivation theory, the ensnarement hypothesis does not rely upon the manifestation of psychological harms but rather argues that within‐prison sanctions generally limit the prosocial opportunities of inmates (Moffitt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such practices are driven by reliance on deprivation theory. Quantitative findings, however, have demonstrated that the hypothesized effects of deprivation (e.g., psychological harm) are rarely associated with within‐prison sanctions (O'Keefe, Klebe, Stucker, Sturm, and Leggett, ; O'Keefe et al., ). Second, consistent with the first limitation, prior scholarship has examined the severity of within‐prison sanctioning with little consideration for the effects of the frequency of within‐prison sanctioning on subsequent antisocial tendencies (Mears, ; Sturgess, Woodhams, and Tonkin, ).…”
Section: Potential For Within‐prison Ensnarementmentioning
confidence: 99%
“…At the same time, as other reviews have emphasized (e.g., Mears, ; O'Keefe et al., ), few of them employ strong research designs with appropriate comparison groups. Also, some studies have found no adverse effects of supermax housing on mental health (see, generally, O'Keefe et al., ; Smith, ). There is, for example, the question of how much worse supermax incarceration affects mental health as compared with what would happen in maximum‐security facilities.…”
Section: Five Key Dimensions Along Which Evidence Is Neededmentioning
confidence: 99%
“…These inmates may also be housed in isolation as a means of protection (Johnston, ). Evidence suggests that—depending on duration and conditions of confinement (O'Keefe et al, )—individuals with serious mental disorders housed in segregation are especially susceptible to deterioration, psychotic break, and suicide ideation (Human Rights Watch , , pp. 33–34; Johnston, ; Shames, Wilcox, & Subramanian, , p. 17).…”
Section: Increased Foreseeable Severity Of Sentencementioning
confidence: 99%